ANALISI ALTERNATIF PEMBANGUNAN PABRIK PEMBEKUAN UDANG VANNAAMEI (L. VANNAMEI) DI KABUPATEN KAUR PROVINSI BENGKULU - Samawi, Ogi Ahmad; Poernomo, Achmad; Permadi, Aef (JURNAL PERIKANAN TROPIS, 2023)
The potential of fisheries in Bengkulu Province is very large. Kaur Regency is one of the regencies in Bengkulu Province, which has a trend of vannaamei shrimp (L. vannamei) production in Kaur Regency which always increases every year. Production of vannamei shrimp (L. vannamei) in 2019 reached 950 tons in 2021, it reached 4,524 tons. This study aims to determine what alternatives can be done for planning the construction of a vannamei shrimp (L. vannamei) freezing plant. This study uses the SWOT analysis method. The results showed that the strategy needed was aggressive. Alternative strategies are; to improve the quality of materials and equipment for cultivation processes; recruit competent workforce in the field of marketing for the expansion of the domestic market; improve the quality of human resources in facing the international market; the vast market share of shrimp provides an opportunity for Kaur Regency to develop a frozen shrimp processing industry which is also strongly supported by the government; build cold storage to accommodate the production of vannamei shrimp (L. vannamei); the government or related stakeholders can immediately build facilities such as an ice factory and add electricity to support the continuity of the shrimp industry in Kaur Regency; increase capital by borrowing from banks or partners to increase production or expand shrimp marketing; and build relationships between the government, stakeholders related to shrimp farmers to collect production results.Keywords: SWOT analysis; Alternative Processing Unit Development Planning